Flutter Analysis of RX-420 Balistic Rocket Fin Involving Rigid Body Modes of Rocket Structures - Andria, Novi (Makara Journal of Technology, 2011)
Flutter Analysis of RX-420 Balistic Rocket Fin Involving Rigid Body Modes of Rocket Structures. Flutter is a phenomenon that has brought a catastrophic failure to the flight vehicle structure. In this experiment, flutter was analyzed for its symmetric and antisymmetric configuration to understand the effect of rocket rigid modes to the fin flutter characteristic. This research was also expected to find out the safety level of RX-420 structure design. The analysis was performed using half rocket model. Fin structure used in this research was a fin which has semispan 600 mm, thickness 12 mm, chord root 700 mm, chord tip 400 mm, made by Al 6061-T651, double spar configuration with skin thickness of 2 mm. Structural dynamics and flutter stability were analyzed using finite element software implemented on MSC. Nastran. The analysis shows that the antisymmetric flutter mode is more critical than symmetric flutter mode. At sea level altitude, antisymmetric flutter occurs at 6.4 Mach, and symmetric flutter occurs at 10.15 Mach. Compared to maximum speed of RX-420 which is 4.5 Mach at altitude 11 km or equivalent to 2.1 Mach at sea level, it can be concluded that the RX-420 structure design is safe, and flutter will not occur during flight.